The Cost-Effectiveness of Antibiotic Prophylaxis for Patients at Risk of Infective Endocarditis. Issue 20 (15th November 2016) - Franklin, Matthew; Wailoo, Allan; Dayer, Mark J.; Jones, Simon; Prendergast, Bernard; Baddour, Larry M.; Lockhart, Peter B.; Thornhill, Martin H.
Abstract : Background: In March 2008, the National Institute for Health and Care Excellence recommended stopping antibiotic prophylaxis (AP) for those at risk of infective endocarditis (IE) undergoing dental procedures in the United Kingdom, citing a lack of evidence of efficacy and cost-effectiveness. We have performed a new economic evaluation of AP on the basis of contemporary estimates of efficacy, adverse events, and resource implications. Methods: A decision analytic cost-effectiveness model was used. Health service costs and benefits (measured as quality-adjusted life-years) were estimated. Rates of IE before and after the National Institute for Health and Care Excellence guidance were available to estimate prophylactic efficacy. AP adverse event rates were derived from recent UK data, and resource implications were based on English Hospital Episode Statistics. Results: AP was less costly and more effective than no AP for all patients at risk of IE. The results are sensitive to AP efficacy, but efficacy would have to be substantially lower for AP not to be cost-effective. AP was even more cost-effective in patients at high risk of IE. Only a marginal reduction in annual IE rates (1.44 cases in high-risk and 33 cases in all at-risk patients) would be required for AP to be considered cost-effective at £20 000 ($26 600) per quality-adjusted life-year. Annual cost savings of £5.5 to £8.2 million ($7.3–$10.9 million) and health gains >2600 quality-adjusted life-years could be achieved from reinstating AP in England. Conclusions: AP is cost-effective for preventing IE, particularly in those at high risk. These findings support the cost-effectiveness of guidelines recommending AP use in high-risk individuals. Abstract : Supplemental Digital Content is available in the text.